2015
DOI: 10.1007/s10461-015-1201-0
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Rates of Depression Among Men Who Have Sex with Men (MSM) Across India: Insights from a Multi-site Mixed Method Study

Abstract: Poor psychosocial health contributes to HIV risk behavior and reduced engagement in treatment and care. This study investigates depression and its correlates among 11,992 MSM recruited via respondent driven sampling in 12 cities across India using the Patient Health Questionnaire-9 and supplemented by analysis of qualitative research from 15 sites with 363 MSM. Overall prevalence of depression was 11 %, with substantial variation across sites and subgroups of MSM, and high prevalence of suicidal thoughts among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 59 publications
5
55
1
Order By: Relevance
“…Existing literature shows MSM and transgenders/ hijras are vulnerable to mental health issues and physical violence from families, sexual partners and legal authorities and that this can be a barrier to PrEP (Chakrapani, Newman, Shunmugam, Logie, & Samuel, 2015; Mimiaga et al, 2013; Sivasubramanian. et al, 2011; Thomas et al, 2011; Thomas et al, 2009b; Tomori et al, 2016). These factors could further invisibilize Indian MSM and trangenders/ hijras , adding to their HIV vulnerability by increasing their closetedness.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Existing literature shows MSM and transgenders/ hijras are vulnerable to mental health issues and physical violence from families, sexual partners and legal authorities and that this can be a barrier to PrEP (Chakrapani, Newman, Shunmugam, Logie, & Samuel, 2015; Mimiaga et al, 2013; Sivasubramanian. et al, 2011; Thomas et al, 2011; Thomas et al, 2009b; Tomori et al, 2016). These factors could further invisibilize Indian MSM and trangenders/ hijras , adding to their HIV vulnerability by increasing their closetedness.…”
Section: Introductionmentioning
confidence: 98%
“…Indian Men who have sex with men (MSM) and transgenders/ hijras are disproportionately impacted by HIV due to limited awareness of HIV, socio-cultural stigma associated with same-sex attraction and gender nonconformity (Kumta et al, 2010; National AIDS Control Organization, 2011; Thomas et al, 2011; Tomori et al, 2016) and criminalization (“Koushal v NAZ Foundation,” 2013). Existing literature shows MSM and transgenders/ hijras are vulnerable to mental health issues and physical violence from families, sexual partners and legal authorities and that this can be a barrier to PrEP (Chakrapani, Newman, Shunmugam, Logie, & Samuel, 2015; Mimiaga et al, 2013; Sivasubramanian.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study with sexual minority women found that isolation, anxiety, high substance use, and suicidal thoughts were common themes in these women's experiences. 35 Prevalence rates for depression, substance abuse and dependence, anxiety, and other psychiatric conditions from varied studies [36][37][38][39][40][41][42][43][44][45][46][47][48][49] are described in Table 1. Badgett 25 stated that in the absence of studies providing a comparable estimate for non-LGBTQIA+ people in India, the population prevalence of a condition can be used as a benchmark.…”
Section: Prevalence Of Mental Health Conditionsmentioning
confidence: 99%
“…While male-to-male sexual contact is common and may not be considered homosexuality (Asthana & Oostvogels, 2001; Khan, 2001; Verma & Collumbien, 2004), identifying as a homosexual and gender non-conformity in behavior or appearance continues to be highly stigmatized (Logie, Newman, Chakrapani, & Shunmugam, 2012; Mimiaga et al, 2014; Sivasubramanian et al, 2011; B. Thomas et al, 2012; Thomas et al, 2009; Tomori et al, 2015). Moreover, cultural norms of masculinity demand marriage to a woman and the procreation of children, leading many MSM to marry and keep their sexual behavior hidden (Asthana & Oostvogels, 2001; Chakrapani, Boyce, & Dhanikachalam, 2011; Chakrapani, Newman, Shunmugam, & Dubrow, 2011; Kumta et al., 2010; Mimiaga et al, 2014; A.…”
Section: Introductionmentioning
confidence: 99%